Features of the course of gestation and birth for asymptomatic bacteriuria in pregnant women, experience and therapeutic aspects - E N Kravchenko; I A Gordeeva (IP Berlin A.V., 2014)
He aim of the study was to examine the peculiarities of gestation and birth for asymptomatic bacteriuria (AB) and to determine the efficacy of antimicrobial therapy in combination with the use of proanthocyanidins. Results: complications during and after childbirth occurred 15 times more often in women with low AB (102-104 CFU/ml) treatment which was not carried out , and 2 times more frequently in the patients with the release of ≥ 105 CFU/ ml and held antibacterial treatment than in the control group. Every sixth pregnant with AB was treated only with antibacterial drugs (8 times more often than in the group of women taking antibiotics in combination with proanthocyanidins) there was a lack of resistant bacterial response.